Advances on P2P, parallel, grid, cloud and internet computing : proceedings of the 11th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2016) November 5-7, 2016, Soonchunhyang University, Asan, Korea - Xhafa, Fatos; Barolli, Leonard; Amato, Flora (Springer, 2016)
P2P, Grid, Cloud and Internet computing technologies have been very fast established as breakthrough paradigms for solving complex problems by enabling aggregation and sharing of an increasing variety of distributed computational resources at large scale. The aim of this volume is to provide latest research findings, innovative research results, methods and development techniques from both theoretical and practical perspectives related to P2P, Grid, Cloud and Internet computing as well as to reveal synergies among such large scale computing paradigms. This proceedings volume presents the results of the 11th International Conference on P2P, Parallel, Grid, Cloud And Internet Computing (3PGCIC-2016), held November 5-7, 2016, at Soonchunhyang University, Asan, Korea.
International conference proceedings.
Includes author index.
Keywords: Parallel processing (Electronic computers) -- Congresses.; Peer-to-peer architecture (Computer networks) -- Congresses.; Computational grids (Computer systems) -- Congresses.; Cloud computing -- Congresses.; elektronické knihy; electronic books